Inclusive Education in Elementary Schools:: an Analysis of Implementation and Policies in SD Negeri 1 Karangwidoro - Nurdiansyah, Alvin; Mohd Puad, Mohd. Hazwan bin (Teunuleh Publisher, 2024)
This study aims to determine the implementation and implementation of inclusive education in SD Negeri 1 Karangwidoro, Malang Regency. Inclusion education seeks to provide equal opportunities for students with special needs to get an education. The method used in this study is a qualitative approach through interviews and direct observation. The subjects of this study are teachers, students with special needs, and observation of social interaction in inclusion classes. The results of this study show that SD Negeri 1 Karangwidoro has a commitment to provide inclusive education despite facing obstacles and obstacles. The biggest obstacles are the absence of accompanying teachers, the availability of infrastructure and facilities, and support from the government as well as the lack of public understanding of inclusive education. Social interaction between regular students and students with special needs shows a positive relationship. This study recommends an increase in teacher training, the provision of infrastructure, and support from the community and the relevant government. In addition, further research is expected to be able to examine more deeply the impact of inclusive education on the academic and social development of students with special needs.